Advances in the characterisation and identification of mastic (Pistacia sp.) resin in archaeological samples by GC-QToF-MS - Tamburini, Diego; Fulcher, Kate; Briggs, Lisa; von Aderkas, Nelly; Pulak, Cemal; Stacey, Rebecca (Royal Society of Chemistry (RSC), 2024)
The optimisation and application of an analytical method based on gas chromatography coupled to quadrupole time-of-flight mass spectrometry (GC-QToF-MS) is proposed for the first time for the characterisation and identification of mastic (Pistacia sp.) resin in archaeological samples. The GC-QToF-MS method demonstrated higher sensitivity compared to single quadrupole GC-MS and enabled enhanced structural elucidation power to be exploited, particularly due to the high mass resolution and accuracy, the possibility to use standard and low ionisation energies as well as its tandem MS capabilities. The heat-induced degradation of the resin was also studied in open air conditions, showing that 28-norolean-17-en-3-one forms upon heating, but then progressively degrades. This makes it a reliable marker for heating of Pistacia resin; however, the lack of detection does not imply that the resin was not heated. These observations were used to interpret the results of a large number of archaeological samples containing Pistacia resin in different formulations, from various archaeological contexts and exposed to different environmental conditions. Lumps of relatively pure resin found in marine waterlogged conditions (Uluburun shipwreck, Turkey), residues on ceramics from Sai Island (Nubia, Sudan) as well as varnish and coating layers on Egyptian coffins from the collections of the British Museum (London, UK) and Fitzwilliam Museum (Cambridge, UK) were analysed to understand what the molecular profiles reveal about the use of the resin. The results showed that the resin was often mixed with a drying or semi-drying oil in ancient varnish formulations, thus suggesting that oil was used as a medium to dissolve the resin, which would have been impossible to apply as a layer using simple heat. These new observations significantly add to our understanding of ancient Egyptian technology and provide museum scientists and conservators with key information to accurately identify Pistacia resin and preserve objects containing it.